DAPK1 Promotes Extrasynaptic GluN2B Phosphorylation and Striatal Spine Instability in the YAC128 Mouse Model of Huntington Disease - Schmidt, Mandi E.; Caron, Nicholas S.; Aly, Amirah E.; Lemarié, Fanny L.; Dal Cengio, Louisa; Ko, Yun; Lazic, Nikola; Anderson, Lisa; Nguyen, Betty; Raymond, Lynn A.; Hayden, Michael R. (Frontiers in Cellular Neuroscience, 2020)
Huntington disease (HD) is a devastating neurodegenerative disorder caused by a CAG repeat expansion in the huntingtin gene. Disrupted cortico-striatal transmission is an early event that contributes to neuronal spine and synapse dysfunction primarily in striatal medium spiny neurons, the most vulnerable cell type in the disease, but also in neurons of other brain regions including the cortex. Although striatal and cortical neurons eventually degenerate, these synaptic and circuit changes may underlie some of the earliest motor, cognitive, and psychiatric symptoms. Moreover, synaptic dysfunction and spine loss are hypothesized to be therapeutically reversible before neuronal death occurs, and restoration of normal synaptic function may delay neurodegeneration. One of the earliest synaptic alterations to occur in HD mouse models is enhanced striatal extrasynaptic NMDA receptor expression and activity. This activity is mediated primarily through GluN2B subunit-containing receptors and is associated with increased activation of cell death pathways, inhibition of survival signaling, and greater susceptibility to excitotoxicity. Death-associated protein kinase 1 (DAPK1) is a pro-apoptotic kinase highly expressed in neurons during development. In the adult brain, DAPK1 becomes re-activated and recruited to extrasynaptic NMDAR complexes during neuronal death, where it phosphorylates GluN2B at S1303, amplifying toxic receptor function. Approaches to reduce DAPK1 activity have demonstrated benefit in animal models of stroke, Alzheimer disease, Parkinson disease, and chronic stress, indicating that DAPK1 may be a novel target for neuroprotection. Here, we demonstrate that dysregulation of DAPK1 occurs early in the YAC128 HD mouse model, and contributes to elevated extrasynaptic GluN2B S1303 phosphorylation. Inhibition of DAPK1 normalizes extrasynaptic GluN2B phosphorylation and surface expression, and completely prevents YAC128 striatal spine loss in cortico-striatal co-culture, thus validating DAPK1 as a potential target for synaptic protection in HD and warranting further development of DAPK1-targeted therapies for neurodegeneration.